2017
DOI: 10.3892/mmr.2017.6224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the phosphorylation of MAPK and protein expression of cyclin D1 in human osteosarcoma tissues

Abstract: The aim of the present study was to investigate the significance of the phosphorylation of mitogen-activated protein kinase (MAPK) and the protein expression of cyclin D1 in human osteosarcoma tissues. Human osteosarcoma tissue samples were collected from 30 patients, benign bone tumor samples were collected from 30 patients, and normal bone tissues were collected from 10 individuals as controls. Immunohistochemistry was performed to measure the levels of phosphorylated (p)-MAPK and cyclin D1 protein in cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…CCND1, located on chromosome 11q13, is a well-known oncogene frequently highly expressed in multiple human cancer types. CCND1 is also overexpressed in OS tissues [17]. OS patients with high CCND1 expression presented with shorter overall survival periods than those of patients with low CCND1 expression [18].…”
Section: Discussionmentioning
confidence: 97%
“…CCND1, located on chromosome 11q13, is a well-known oncogene frequently highly expressed in multiple human cancer types. CCND1 is also overexpressed in OS tissues [17]. OS patients with high CCND1 expression presented with shorter overall survival periods than those of patients with low CCND1 expression [18].…”
Section: Discussionmentioning
confidence: 97%
“…Cyclin D1 is a key molecule for cells to transform from G1 phase to S phase (20). siRNA targeting Cyclin D1 can interfere with the expression of Cyclin D1 (21). This leads to tumor cell arrest in G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to tumor cell arrest in G1 phase. Inhibition of Cyclin D1 expression can change the distribution pattern of the cell cycle (21). The proportion of G0/1 phase increases, S phase decreases and G1/S increases significantly, indicating cell cycle arrest at G1/S.…”
Section: Discussionmentioning
confidence: 99%
“…CCND1 encoding Cyclin D1 is a member of cyclin family and plays a key role in regulating cell cycle progression ( 22 ). Increasing evidence indicated that CCND1 exerts an essential role in promoting the development and progression of human cancers, such as gastric cancer ( 23 ), glioma ( 24 ), renal cell cancer ( 25 ), lung adenocarcinoma ( 26 ) and ( 27 ). Except regulation of cell cycle, recent reports also indicated that CCND1 has a pivot role in promoting migration and tumor metastasis ( 28 ).…”
Section: Discussionmentioning
confidence: 99%